Factors Impeding Health-Care Professionals to Effectively Treat Coronavirus Disease 2019 Patients in Pakistan: A Qualitative Investigation - Raza, Ali; Matloob, Sheema; Abdul Rahim, Noor Fareen; Abdul Halim, Hasliza; Khattak, Amira; Ahmed, Noor Hazlina; Nayab, Durr-e-; Hakeem, Abdul; Zubair, Muhammad (Frontiers in Psychology, 2020)
The coronavirus disease 2019 (COVID-19) pandemic, first reported in late December 2019, is regarded as the most significant public health emergency of the century. According to the World Health Organization (WHO), the current outbreak of COVID-19 has affected millions of people and killed hundreds of thousands in more than 200 countries, including Pakistan. Health-care professionals (HCPs) cannot minimize human interactions or isolate themselves from patients due to their jobs and moral duties. Hence, the outbreak needed HCPs to work in adverse and challenging conditions with possible mental health problems. In light of the stated background, this study aims to explore and understand the factors that impede HCPs to effectively treat COVID-19 patients in Karachi, Pakistan. Based on qualitative methods, a phenomenological approach was considered to record the true experiences of HCPs. Twelve doctors and nurses were recruited from five COVID-19 designated hospitals in Karachi, Sindh Province, using purposive and snowball sampling. Semi-structured in-depth telephone interviews were conducted from April 6 to 14, 2020, and analyzed through thematic analysis. The findings suggest that there were two types of constraints, institutional and personal, which were impeding HCPs to treat COVID-19 patients effectively. Institutional constraints include the poor condition of isolation wards, inadequate availability of personal protective equipment (PPE), excessive and uneven workload, and absence of emotional and psychological support in hospitals. Besides, personal constraints include nervousness due to the novel virus, a constant fear of becoming infected, fear of taking virus to family, extreme isolation and loneliness, and feeling of powerlessness. The study found that HCPs in Pakistan have been dealing with a high risk of infection, causing mental health problems such as stress, anxiety, and depressive symptoms. These mental health problems not only affect attention, understanding, and decision-making capacity of HCPs, which could hinder the fight against COVID-19, but they could also have a continuous effect on their overall well-being on a long-term basis. Therefore, the present study outlines important clinical and policy strategies that are needed to support HCPs as the pandemic continues.